CT Scan-Measured Pulmonary Artery to Aorta Ratio and Echocardiography for Detecting Pulmonary Hypertension in Severe COPD - Iyer, Anand S. (American College of Chest Physicians, 2014)
BACKGROUND: COPD is associated with significant morbidity primarily driven by acute exacerbations. Relative pulmonary artery (PA) enlargement, defined as a PA to ascending aorta (A) diameter ratio greater than one (PA:A > 1) identifies patients at increased risk for exacerbations. However, little is known about the correlation between PA:A, echocardiography, and invasive hemodynamics in COPD. METHODS: A retrospective observational study of patients with severe COPD being evaluated for lung transplantation at a single center between 2007 and 2011 was conducted. Clinical characteristics, CT scans, echocardiograms, and right-sided heart catheterizations were reviewed. The PA diameter at the bifurcation and A diameter from the same CT image were measured. Linear and logistic regression were used to examine the relationships between PA:A ratio by CT scan and PA systolic pressure (PASP) by echocardiogram with invasive hemodynamics. Receiver operating characteristic analysis assessed the usefulness of the PA:A ratio and PASP in predicting resting pulmonary hypertension (PH) (mean pulmonary artery pressure [mPAP] > 25 mm Hg). RESULTS: Sixty patients with a mean predicted FEV(1) of 27% ± 12% were evaluated. CT scan-measured PA:A correlated linearly with mPAP after adjustment for multiple covariates (r = 0.30, P = .03), a finding not observed with PASP. In a multivariate logistic model, mPAP was independently associated with PA:A > 1 (OR, 1.44; 95% CI, 1.02-2.04; P = .04). PA:A > 1 was 73% sensitive and 84% specific for identifying patients with resting PH (area under the curve, 0.83; 95% CI, 0.72-0.93; P < .001), whereas PASP was not useful. CONCLUSIONS: A PA:A ratio > 1 on CT scan outperforms echocardiography for diagnosing resting PH in patients with severe COPD.